2019
DOI: 10.4081/ijfs.2019.7956
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase-producing bacteria in food-producing animals, wildlife and environment: A challenge for human health

Abstract: Antimicrobial resistance is an increasing global health problem and one of the major concerns for economic impacts worldwide. Recently, resistance against carbapenems (doripenem, ertapenem, imipenem, meropenem), which are critically important antimicrobials for human cares, poses a great risk all over the world. Carbapenemases are β-lactamases belonging to different Ambler classes (A, B, D) and encoded by both chromosomal and plasmidic genes. They hydrolyze a broad variety of β-lactams, including carbapenems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 155 publications
(192 reference statements)
2
79
0
1
Order By: Relevance
“…Carbapenems are not routinely used in food animal production including poultry farming; however, carbapenem resistance in the E.coli isolates might have coevolved along with resistance to other antibiotics that are commonly used in resistant strains of bacteria may also be disseminated through direct contact, insect vectors, and other animals [8,13,14]. An earlier study by Poirel et al [15] also suggested that co-selection of carbapenemase genes under the selection pressure imposed by the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 2 November 2020 doi:10.20944/preprints202011.0065.v1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbapenems are not routinely used in food animal production including poultry farming; however, carbapenem resistance in the E.coli isolates might have coevolved along with resistance to other antibiotics that are commonly used in resistant strains of bacteria may also be disseminated through direct contact, insect vectors, and other animals [8,13,14]. An earlier study by Poirel et al [15] also suggested that co-selection of carbapenemase genes under the selection pressure imposed by the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 2 November 2020 doi:10.20944/preprints202011.0065.v1…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the phylogenetic groups of the E. coli isolates was determined according to the protocols described by Clermont et al [8]. Briefly, a single PCR reaction mixture containing 12. supplied by Integrated DNA Technologies (Singapore).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidences exist that the transmission of resistance might have taken place from animals to humans. Although many of these evidences were not direct and were based on the similarities between the carbapenem resistance genes of bacteria isolated from food-producing animals including poultry, pigs, cattle and from humans having close contact with these animals such as farm workers, animal caretakers and their family members [ 128 ]. To support risk assessment for zoonotic CRE, a comprehensive systematic review on CRE that carried bla VIM , bla KPC , bla NDM , blaIMP and bla OXA , from wildlife, food-producing, and companion animals was conducted recently by Köck, el al [ 72 ].…”
Section: Molecular Epidemiology Of Carbapenem Resistance (Cr) Genementioning
confidence: 99%
“…Another study by Li et al [ 124 ], investigated the prevalence, risk factors, and drivers of CRE transmission between humans and their backyard animals in rural China that provided direct evidence of inter-host transmission of bla NDM producing E. coli between humans and backyard animals. Moreover, the incidence of carbapenem resistant genes in food-producing animals has also been reported from several other countries with chickens and pig being the most investigated species, in which carbapenem resistant genes has been most frequently detected [ 128 ].…”
Section: Molecular Epidemiology Of Carbapenem Resistance (Cr) Genementioning
confidence: 99%